A randomized controlled trial of the effectiveness of the mHealth program in improving the lifestyle of nursing students - Shaherah Yousef Andargeery; Dina S. El-Rafey (Scientific Reports)
Abstract Promoting healthy lifestyles is essential for preventing chronic diseases, yet a vast majority of university students regularly engage in unhealthy habits. Utilizing mobile smart devices for health interventions, known as mHealth, which integrate behavioral change theories with environmental interaction, offers a promising and cost-effective strategy to encourage lasting adoption of healthier habits. This study compared the effectiveness of the mHealth intervention program with a traditional face-to-face program in fostering healthy lifestyle changes. Through a randomized controlled trial involving 220 nursing students (110 in the mHealth intervention program and 110 in the traditional program), data were collected from May to December 2023 using predefined questionnaires. These questionnaires included the Global/International Physical Activity Questionnaire (GPAQ/IPAQ) for monitoring adult physical activity, a Food Frequency Questionnaire (FFQ) for dietary assessment, and a Sleep Quality Scale (SQS). Three months after the educational intervention program, lifestyle improvements were significantly more pronounced in the mHealth intervention group compared to the traditional group. The implementation of the mHealth intervention program aimed at improving lifestyle has proven to be a transformative approach in fostering positive behavioral changes among participants. The study was approved by the IRB of Zagazig Faculty of Medicine (IRB 10827/24-6-2023) and was registered at the ClinicalTrials.gov (NCT06404619, 08/05/2024).